The potential application of blockchain technology to guarantee claims on sustainability, ethics, provenance, and authenticity in the fragrance industry - Das, Surajit (2023)
Recently, digitalization of the supply chain is gaining huge attention. In this space, blockchain technology is being explored in the supply chain by different industries for its immutability, transparency and traceability functions. This research aims to investigate the usefulness of blockchain technology in the fragrance industry’s supply chain to make the supply chain activities traceable and transparent to its stakeholders. This research specifically focused on the ability of blockchain to support provenance, sustainability, ethical, and authenticity of the fragrances and fragrance raw materials (RMs). An extensive literature review has been performed on relevant claims in the fragrance industry, its supply chain complexities, current solutions on traceability, and needs on robust supply chain transparency and traceability. Additionally, detail literature review on blockchain technology and its utility in supply chain management has been performed.